Cobalamin Deficiency in Metformin Treated Type 2 Diabetics Presenting at a Tertiary Care Hospital of Sindh - Haji Khan Khoharo, Ali Akbar Shah, Fatima Qureshi, Tabinda Taqi, Mujahid All Chandio, Salma Memon , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To determine vitamin B,, levels in metformin treated type 2 diabetes mellitus and its correlation with dose and duration of metformin. Methods: This Cross sectional study was conducted at Isra University Hospital, Hyderabad from June 2016 to December 2017. A sample of 200 type 2 diabetics was divided into 2 groups: Group 1 - type 2 diabetics taking metformin and Group 2 - type 2 diabetics without metformin were selected. Serum cobalamin levels were measured from the sera by ELISA assay kit (Chemiluminescence Technique using Abbot Architect 1000). Variables were statistically analyzed. Results: Serum cobalamin in metformin treated diabetics was noted as 159.6±35.7 pgidl compared to 232.5±28.5 1 pg/c11 (P=0.000 1 ). Serum cobalamin in male was 211.6+16.7 pgiml compared to 135.35±15.51 pg/m1 in female (P=0.0001). Cobalamin deficiency was noted in 49% metforrnin treated diabetics compared to 37% in no-metformin diabetics. Conclusion: Long term metformin drug therapy is significantly associated with cobalamin deficiency. Cobalamin screening and supplements should be offered to metformin treated diabetics.